RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN TENAGA PENGAJAR DENGAN METODE FUZZY INFERENCE SYSTEM (FIS) MAMDANI - Sumitre, Made; Kurniawan, Rio (Jurnal Informatika, 2014)
The process of acceptance of lectures in STAH Lampung has an obstacle which is the duration of the data management process and subjectivity of decision taking especially because some of candidates which do not have different ability. This obstacle impacts in the duration of decision making process for lectures acceptance. Fuzzy logic is used as a way to map the problem fromÂ  input to output, the process of decision taking of lectures acceptance is using Mamdani Fuzzy method which is known as max-min method. The input variables that are used are IPK, experience, interview, and the interest variables while the output is final score. The selection process troughs several steps which are fuzzy group creating, implication function application, the rules composition, and defuzzy. This decision supporting system of lectures acceptance selection by using Mamdani FIS is able to give the specific and right score which is suitable with institution standard z â¥ 50 score.Key Words : STAH, Lecture, Decision Supporting System